Peningkatan Kreatifitas Anak Sanggar Seni Kololio Kabupaten Sigi melalui Pelatihan Penganekaragaman Kreasi berbasis Budaya Suku Kaili - Sabang, Sri Mulyani; Ijirana, Ijirana; Syamsuriwal, Syamsuriwal; Misnah, Misnah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This Community Service Program (PKM) aims to enhance the creativity of children and adolescents at Sanggar Seni Kololio, Sigi Regency, through training in creative diversification based on the Kaili ethnic culture. This program was initiated due to the low literacy rate and environmental awareness among children in Kaleke Village. The project has two main focuses: improving literacy and increasing environmental awareness. Literacy improvement is achieved by establishing a Reading Corner (Pondok Baca) filled with various activities such as free reading, storytelling, book discussions, and reading journals. Meanwhile, environmental awareness is increased through activities like creating herbariums and insectariums, making trash cans from plastic waste, and crafting handicrafts from recycled materials. The program utilizes a participatory approach, actively involving the community in every stage of the process. The implemented methods include education, training, empowerment, demonstration, and appreciation. The expected output of this activity is the documentation of community service activities in the form of a scientific article. The target achievements of this project include increasing children's interest in reading, environmental awareness, and skills, as well as the availability of an adequate Reading Corner. The results of this PKM activity indicate that the program has run well and achieved its objectives. Indicators of the program's success include increased creativity of children and adolescents, diversification of artistic creations, strengthening the capacity of Sanggar Seni, and community empowerment.